Pharmacological Insight Among Medical Students and Implications for Practice Ethics - Achdi Kurnia (Sinteza, 2026)
This cross-sectional quantitative study aims to analyse the level of pharmacological knowledge among medical students and to examine its association with reduced potential violations in medical practice. The study involved 105 active students from the Medical Education Study Program at Universitas Muhammadiyah Prof. Dr HAMKA (UHAMKA) and used a Likert-scale questionnaire. Data were analysed using descriptive statistics and simple linear regression. The results show a statistically significant moderate association between pharmacological knowledge and the reduction of potential violations. These findings suggest that pharmacological knowledge is related to safer self-reported practices among medical students. Nevertheless, this study has several limitations, including reliance on self-reported data, a single-institution sample, and the lack of a fully validated instrument to measure potential violations. Therefore, the results reflect statistical association rather than causation. Future studies are recommended to use larger, multicentre samples, validated measurement tools, and more robust analytical approaches to understand better the relationship between pharmacological knowledge and safe medical practice.